2013
DOI: 10.1128/aem.00537-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Virulence Factors Characteristic of Human Escherichia coli Pathotypes and Antimicrobial Resistance in O157:H7 and Non-O157:H7 Isolates from Livestock in Spain

Abstract: eThe distribution of virulence factors (VFs) typical of diarrheagenic Escherichia coli and the antimicrobial resistance (AMR) profiles were assessed in 780 isolates from healthy pigs, broilers, and cattle from Spain. VF distribution was broader than expected, although at low prevalence for most genes, with AMR being linked mainly to host species. P athogenic isolates of Escherichia coli are characterized by the presence of virulence factors (VFs) that can be combined, leading to different pathotypes (1). Six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…It seems that the detection of stx 1 alone or in combination with stx 2 is less frequent than the carriage of stx 2 alone. This fact may indicate that in Spain, O157:H7 from wild animals are similar to those of cattle regarding their VFs combination (Cabal et al 2013). However, in other countries, stx 2 was more frequently detected than the other two patterns in cattle (Ateba & Mbewe 2011).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It seems that the detection of stx 1 alone or in combination with stx 2 is less frequent than the carriage of stx 2 alone. This fact may indicate that in Spain, O157:H7 from wild animals are similar to those of cattle regarding their VFs combination (Cabal et al 2013). However, in other countries, stx 2 was more frequently detected than the other two patterns in cattle (Ateba & Mbewe 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Oppositely, antimicrobial resistance has been found in Salmonella and indicator E. coli from wildlife and livestock, including resistance to fluoroquinolones and cephalosporines (Navarro-Gonzalez et al 2012, which is of concern for public health. Cabal et al (2013) reported high frequency of antimicrobial resistance in E. coli O157:H7 from healthy cattle in Spain. This suggests that the E. coli O157:H7 strains from wildlife might be genetically different to those in livestock, and that the sources of infection might be different for livestock and wildlife.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cabal et al 42 compared the virulence gene profile of E. coli isolated from cattle, swine and broiler. The results indicated the presence of stx1 and stx2 gene (from both O157:H7 and Non-O157:H7 E. coli serotypes) in cattle and swine42.…”
Section: Discussionmentioning
confidence: 99%
“…For the comparison of our data with that from intensively reared livestock, Table 2 shows the frequencies of resistant E. coli in cattle from Spain (26).…”
mentioning
confidence: 99%